Respostas

2014-01-06T13:48:44-02:00
X² - 6x + 9
a = 1 b = -6 c = 9
Δ = b²-4.a.c
Δ = -6²- 4*1*9
Δ = 36 -36
Δ = 0

x' = -b +√Δ /2.a
x' = 6 + 0/2
x' = 3

x" = 6 - 0/2
x" = 3
Neste caso a solução é S = 3, 3
2014-01-07T03:25:49-02:00
X² - 6x + 9 = 0
a = 1                   b = - 6                   c = 9
Δ = b² - 4 . a . c
Δ = (- 6)² - 4 . 1 . 9
Δ = 36 - 36
Δ = 0
Quando o delta for 0 (zero) teremos duas raízes reais e iguais.
x = - b ± √Δ
     -----------------
         2 . a
x = - (- 6) ± √0
     ------------------
           2 . 1
x = 6 ± 0
     ----------
        2
x' = 6 
÷ 2
x' = 3
x" = 3
 
Resposta: {3; 3}